Association between handgrip strength and bone mineral density of Brazilian children and adolescents stratified by sex: a cross-sectional study - Bruna Thamyres Ciccotti Saraiva; Ricardo Ribeiro Agostinete; Ismael Forte Freitas Júnior; Daniel Eduardo Rodrigues de Sousa; Luis Alberto Gobbo; William Rodrigues Tebar; Diego Giulliano Destro Christofaro (BMC, 2021)
Abstract Background To examine the association of handgrip strength (HGS) and bone mineral density (BMD) of Brazilian children and adolescents. Methods The sample included 243 children and adolescents aged from 4 to 15 years (9.3 ± 2.2 years), 171 males and 72 females. The following measurements were performed: weight, height, trunk length, and years to the peak height velocity (PHV). The percentage lean soft tissue (PLST), percentage fat mass (PFM), and BMD were obtained using Dual Energy X-ray Absorptiometry (DXA) and HGS using a dynamometer. Results In girls, HGS was positively associated with higher BMD, even after the adjustments, by arms [β = 0.006; p < 0.001], legs [β = 0.014; p < 0.001], pelvis [β = 0.019; p < 0.001], trunk [β = 0.013; p < 0.001], spine [β = 0.013; p = 0.008], and total body [β = 0.009; p < 0.001]. The same occurred in the boys, even after the adjustments a positive relationship was observed, whereas higher HGS was related to greater BMD in arms [β = 0.006; p < 0.001], legs [β = 0.017; p < 0.001], pelvis [β = 0.014; p < 0.001], trunk [β = 0.009; p < 0.001], spine [β = 0.008; p < 0.001], and total body [β = 0.007; p < 0.001]. Conclusion HGS was positively associated to BMD in boys and girls, regardless of age, PHV, PLST, and PFM.